Pengaruh Profitabilitas, Likuiditas, Leverage, dan Aktivitas terhadap Nilai Perusahaan yang Dimoderasi Corporate Social Responsibility - Vicky Ardian; Ickhsanto Wahyudi (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this study is to analyze the effect of profitability, liquidity, leverage, activity on firm value moderated by corporate social responsibility. This study uses data collected from financial reports from the Indonesia Stock Exchange (IDX) using purposive sampling which fulfills the exploratory steps. The period used in the study was 5 years, namely 2016 to 2020 with the amount of data used being 60 samples of LQ45 index companies. The research method uses SPSS version 26 with secondary data types. The results of the study state that profitability positively affects firm value, while liquidity, leverage, and activity do not affect firm value. The results of the moderating variable state that Corporate Social Responsibility is able to moderate profitability on firm value while Corporate Social Responsibility in this study is not able to moderate liquidity, leverage, and activity on firm value.